Changes in amounts of total salivary gland proteins of Lutzomyia longipalpis (Diptera: Psychodidae) according to age and diet - Prates, D. B.; Santos, L. D. [UNESP]; Miranda, J. C.; Souza, A. P A; Palma, Mario Sergio [UNESP]; Barral-Netto, M.; Barral, A. (My University, 2008)
Saliva plays important roles in facilitation of a bloodmeal, lubrication of mouthparts, and parasite transmission for some vector insects. Salivary composition changes during the lifetime of an insect, and differences in the salivary profile may influence its functions. In this report, the amount and profile of salivary gland protein of the American visceral leishmaniasis vector Lutzomyia longipalpis (Lutz & Neiva, 1912) were analyzed at different times of insect development and diet. Protein content from unfed female sand flies increased significantly with age, and a significant difference was observed in sugar-fed females during the first 10 d of adult life. Salivary protein content sharply decreased 1 d after blood feeding, with gradual increase in concentration the following days. SDS-polyacrylamide gel electrophoresis analysis revealed that most polypeptides present in the saliva of sugar-fed also were present in the saliva of blood-fed females. Understanding changes in sand fly's saliva contents at distinct days after emergence and the influence of a bloodmeal in this aspect may reveal the role played by saliva during leishmaniasis transmission. © 2008 Entomological Society of America.
Keywords: Lutzomyia longipalpis; Saliva; Salivary gland; SDS-polyacrylamide gel electrophoresis; insect protein; saliva protein; aging; animal; diet; female; gene expression regulation; metabolism; physiology; Psychodidae; Aging; Animals; Diet; Female; Gene Expression Regulation; Insect Proteins; Salivary Proteins; Diptera; Hexapoda; Phlebotominae